Self-improvement an essay in Kantian ethics - Johnson, Robert N. (Oxford : Oxford University Press, 2011)
Is there any moral obligation to improve oneself? Robert N. Johnson argues that there is, and develops a broadly Kantian point of view to defend his position and challenge a range of opposing arguments.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 20, 2012).
Includes bibliographical references and index.
Keywords: Kant, Immanuel, -- 1724-1804.; Self-culture.; Self-actualization (Psychology); Ethics